Pemikiran Ki Hadjar Dewantara Dan Kebijakan Merdeka Belajar - Yan Nurcahya; Widiati Isana; Deri Sugiarto; M Kautsar Thariq Syah (Advances In Education Journal, 2025)
Ki Hadjar Dewantara through Taman Siswa has inherited the embryo of an education system based on local Indonesian culture. Teaching in Taman Siswa is based on two main principles, namely among and pamong. The principle of among places students as the main target and priority that must be "served". Meanwhile, pamong emphasizes the teacher's task to provide facilities, motivation, inspiration and conditions for students to learn according to their desires and abilities to learn individually or student learning independence. His thoughts on education for the Indonesian nation, one of which is the foundation for releasing colonialism from the Netherlands. The method used by the author in this article is the historical research method. The historical method used in this article consists of four stages, namely heuristic, verification, interpretation. The application of education for Indonesian citizens in general, without classifying the economic and racial capabilities of citizens at that time, contributed greatly to the Indonesian nation in advancing education and national thinking.